Compliance and Effectiveness Evaluation of Environmental Management and Monitoring Plans (UKL–UPL) in the Calcium Carbonate Milling Industry: A Case Study of PT X - Lia Nita Arizahro; Khuliyah Candraning Dinayah; Kurdiyono K (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
PT X is a company that is required to report the Environmental Management and Monitoring Efforts (UKL–UPL) and has obtained an Environmental Permit. In accordance with Government Regulation Number 22 of 2021 Article 49, PT X is obliged to implement environmental management and monitoring measures and submit reports on a semester basis. This study evaluates the compliance and effectiveness of the implementation of the UKL–UPL for Semester II of 2023–2024 at PT X. The research applies an empirical juridical method with a descriptive-comparative analysis of UKL–UPL documents and laboratory test results. The findings indicate that the company has complied with environmental permitting requirements, environmental quality standards, domestic wastewater quality testing, and hazardous and toxic waste (B3) management. However, increases in Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammonia, and ambient air particulate parameters were observed, indicating a decline in environmental quality. In addition, the monitoring frequency has not fully complied with regulatory provisions. It is concluded that administrative compliance has been achieved; however, the effectiveness of environmental control still needs to be improved through routine monitoring and the integration of digital reporting systems.